A Theory of Racialized Organizations. Issue 1 (February 2019) - Ray, Victor
Organizational theory scholars typically see organizations as race-neutral bureaucratic structures, while race and ethnicity scholars have largely neglected the role of organizations in the social construction of race. The theory developed in this article bridges these subfields, arguing that organizations are racial structures—cognitive schemas connecting organizational rules to social and material resources. I begin with the proposition that race is constitutive of organizational foundations, hierarchies, and processes. Next, I develop four tenets: (1) racialized organizations enhance or diminish the agency of racial groups; (2) racialized organizations legitimate the unequal distribution of resources; (3) Whiteness is a credential; and (4) the decoupling of formal rules from organizational practice is often racialized. I argue that racialization theory must account for how both state policy and individual attitudes are filtered through—and changed by—organizations. Seeing race as constitutive of organizations helps us better understand the formation and everyday functioning of organizations. Incorporating organizations into a structural theory of racial inequality can help us better understand stability, change, and the institutionalization of racial inequality. I conclude with an overview of internal and external sources of organizational change and a discussion of how the theory of racialized organizations may set the agenda for future research.